Aseptic Germination and Agrobacterium rhizogenesmediated Transformation of Taraxacum hybernum Steven (Plant Tissue Culture and Biotechnology, 2017)
Taraxacum hybernum Steven, also known as krym‐saghyz, is one of the potential sources of natural rubber. The authors studied the aseptic germination of the T. hybernum seeds using various sterilizing agents and their effect on contamination. In vitro T. hybernum plants were used for Agrobacterium rhizogenesmediated transformation. A4 and 15834 strains of A. rhizogenes showed similar effectiveness after inoculation by injection into the hypocotyls. Authors generated the hairy roots of T. hybernum and the transgenic forms of this plant using A. rhizogenes‐mediated transformation.Plant Tissue Cult. & Biotech. 27(2): 141-151, 2017 (December)